Benzodiazepine abuse among athletes: pain relief or just a weapon against insomnia? A clinical case study - Zamboni, L.; Lugoboni, F.; Zandonai, T. (Scandinavian Journal of Medicine & Science in Sports, 2019)
It is widely recognised that benzodiazepine abuse can potentially induce addiction. Benzodiazepine addiction among athletes is a new and growing phenomenon that we are encountering among our patients. We describe a case of lormetazepam addiction in a female competitive marathon runner. A 30-year-old female elite athlete developed lormetazepam addiction after increasing her daily benzodiazepine dosage in an attempt to achieve better sleep and enhanced performances during training. She was hospitalised for 7 days to undergo benzodiazepine detoxification. Her lormetazepam daily dosage on admission was 18 vials (20 ml x 18 = 360 ml). This report highlights the risk of athletes becoming addicted to benzodiazepines used to combat insomnia and pain. There is a need for clinical and epidemiological research to investigate the effects of this addiction, with a view to better protecting the health of athletes.